Spectroscopic Techniques for Characterization of Nanomaterials - Alessio, Priscila; Aoki, Pedro H.B.; Furini, Leonardo N.; Aliaga, Alvaro E.; Leopoldo Constantino, Carlos J. (Elsevier, 2017)
This chapter discusses the characterization of nanomaterials, that is, nanoparticles and nanometer(s)-thick thin films. The focus is on the application of ultraviolet-visible (UV-vis) spectroscopy, infrared (IR) absorption spectroscopy, Raman scattering, and surface-enhanced Raman scattering (SERS) for nanomaterial characterization. This chapter will present literature studies that applied spectroscopic techniques to nanomaterial characterization, and these studies can be used by the reader to investigate his/her own nanostructured systems. The selected articles are discussed as case studies to provide information on the spectroscopic techniques. The theoretical foundations related to each technique and a discussion of their respective measurement systems (devices) are not included in this chapter.
Keywords: Infrared; Molecular organization; Nanoparticles; Nanostructures; Raman scattering; SERS; Spectroscopy; Surface-enhanced Raman scattering; Thin films; UV-vis